Assessing the Impact of Greenhouse Gas Emissions and UV Index on Climate Changes in Iraq - Potrous, Saad M. (Geography, Earth Science and Environment: Research Highlights Vol. 4, 2025)
Climate change in Iraq has an impact that makes Iraq's environmental challenges. The environment is deteriorating due to greenhouse gas emissions causing global warming. Greenhouse gases (CO2, CH4, H2O) absorb the sun’s heat that radiates from the Earth’s surface, trap it in the atmosphere, and prevent it from escaping into space The greenhouse effect keeps the Earth’s temperature warmer. Measurements of the emissions of greenhouse gases including Carbon Dioxide (CO2) and Methane (CH4) were taken for Iraq. UV Index charts for the Southern region of Iraq (Basra Province), Central region (Baghdad Province) and Northern region (Duhok Province) for the Summer and Winter seasons of 2024 are shown in this work. Results indicated that Carbon Dioxide (CO2) is emitted in larger quantities, particularly in Iraq, due to its heavy reliance on fossil fuels for power generation, transportation, and industry. While Methane (CH4) is emitted in larger quantities compared to (CO2), it is a far more potent greenhouse gas, where Methane has about 25 times the global warming potential of carbon dioxide (CO2). Values of the UV Index in Iraq illustrated that the three regions (Basra, Baghdad and Duhok) during the Summer and Winter Seasons (2024), confirmed a big difference between the two seasons. The results indicate an increase and decrease in the values of the (UV) Index between the Summer and Winter seasons due to the proximity and distance of the Earth from the Sun in its circular motion in the elliptical orbit around the Sun.